2021
DOI: 10.1177/2045125321991277
|View full text |Cite
|
Sign up to set email alerts
|

Long-acting injectable aripiprazole in pregnant women with schizophrenia: a case-series report

Abstract: Antipsychotic long-acting formulations (LAI-AP) have emerged as a new therapeutic choice to treat patients presenting a severe mental disorder. Despite that, to date, there is a lack of safety data and studies regarding the use of LAI-AP formulations in pregnant women. Here we present the first six-case series of pregnant women with schizophrenia treated with aripiprazole-LAI reported in the literature. All patients remained psychopathologically stable through pregnancy and the postpartum period, and all of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 55 publications
(96 reference statements)
0
7
0
Order By: Relevance
“…Of these 200 publications, 17 met the inclusion criteria, and 183 were excluded (172 irrelevant publications, 6 review/consensus guidelines, 3 publications with unavailable full text, 1 conference abstract of an already included publication, and 1 conference abstract with incomplete data on pregnancy and delivery outcomes). We identified 2 additional publications via citation search; therefore, 19 publications satisfied the inclusion criteria: 3 case series[ 20 , 21 , 33 ], 15 case reports[ 34 - 48 ], and 1 conference abstract[ 49 ]. One case series reported aggregate data[ 20 ], while all others reported individual data.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of these 200 publications, 17 met the inclusion criteria, and 183 were excluded (172 irrelevant publications, 6 review/consensus guidelines, 3 publications with unavailable full text, 1 conference abstract of an already included publication, and 1 conference abstract with incomplete data on pregnancy and delivery outcomes). We identified 2 additional publications via citation search; therefore, 19 publications satisfied the inclusion criteria: 3 case series[ 20 , 21 , 33 ], 15 case reports[ 34 - 48 ], and 1 conference abstract[ 49 ]. One case series reported aggregate data[ 20 ], while all others reported individual data.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 23 babies born alive who were exposed to aripiprazole LAI, one[ 21 ] experienced postural plagiocephaly and hypertonia during the first 6 wk of life that resolved with physiotherapy (he developed normally during the 3-year follow-up), one[ 21 ] remained in the incubator for 1 month due to prematurity (but developed normally during the 2-year follow-up), and one[ 33 ] was born preterm with Down’s syndrome, developed fetal hydrops complicated by septic shock and massive anuria, and died within 10 d (but this syndrome cannot be considered a drug-induced malformation).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In spite of the large experience with the use of the same molecules by oral route without adverse effects on the newborn [ 1 ], there is still some concern on the use of these LAIs in pregnancy. Information is limited to few case studies and case series: inconsistent outcomes have been documented, including some negative outcomes (prematurity, babies being small for gestational age, congenital anomalies and neonatal adjustment problems), which are difficult to generalize [ 2 , 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that the disturbance in glucose during pregnancy can increase the risk of gestational mellitus diabetes [ 20 ]. Several studies have shown that ARI, both oral form, and long-acting injection, was not associated with an increased risk of major congenital defects and neurological malformations [ 21 23 ]. Surprisingly, it was established that ARI (10–20 mg/day) has the potency to normalize significantly elevated levels of serum prolactin caused by antipsychotic-induced prolactinemia [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%